Massage Therapy For Breast Cancer Complaint - Susan Susyanti; Aneng Y; Rachmat Ch (Jurnal Medika Cendikia, 2015)
Breast cancer is one of the leading causes of cancer death, usually affects women aged 18- 54 years, especially high risk in women aged 45 years, amounting to 25% (Lee, 2008). Based on the results of research on breast cancer, there were 26 cases per 100,000 women with breast cancer each year. The existence of the phenomenon certainly brings concern for all of us to the risk of increasing the incidence of breast cancer. During the various treatments performed on patients with breast cancer, such as surgery, chemotherapy, radiation, and hormone therapy. Therapy is not always profitable and successful, but can cause side effects. Recent research suggests non-pharmacological treatment such as self-hypnosis, relaxation, massage and acupressure therapy proven to reduce the side effects of chemotherapy. Massage therapy as an alternative treatment proven to reduce a variety of physical complaints / psychological result of chemotherapy. Various journals have published the results of research on the positive effects of massage therapy in relieving many complaints in patients with breast cancer due to chemotherapy and radiation therapy. Data collected in the form of literary journals that published research results, traced using CINAHL-EBSCOhost, ProQuest, PubMed, HealthMed Journal, with the key word "Breast Cancer", "Massage Therapy", and in between. It also searches done through Google search engine using the filetype pdf. Finally found the article as much as 5 years of publication in the 2000s, that between the years 2004-2011. The inclusion criteria used were each journal that discusses the influence of massage therapy in reducing the various complaints in patients with breast cancer, with English literature in the form of full articles ranging from abstract to conclusion. In general, the conclusions from this literature review that massage therapy can be used as an alternative non- pharmacological treatments to reduce the perceived grievances of patients as a side effect of breast cancer treatment